2013
DOI: 10.1097/sla.0b013e31827e52e1
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Induction of Cell Membrane CD47 Limits Basal and Temperature-Induced Changes in Cutaneous Blood Flow

Abstract: Objective We tested the hypothesis that the matricellular protein thrombospondin-1 (TSP1), through binding to and activation of the cell receptor CD47, inhibits basal and thermal-mediated cutaneous blood flow. Background Data Abnormal and decreased cutaneous blood flow in response to temperature changes or vasoactive agents is a feature of cardiovascular disease and aging. The reasons for decreased cutaneous blood flow remain incompletely understood. Further, a role for matricellular proteins in the regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 54 publications
4
35
1
Order By: Relevance
“…Mechanistic studies demonstrated that TSP1 blocked the dephosphorylation of myosin light chain-2 induced by treating these cells with NO and thereby promoted F-actin assembly and contraction of the smooth muscle cells. Notably, the elevated tissue cGMP levels found in young male Thbs1 -/-mice persisted as those mice were aged to 12-16 months, but cGMP levels fell significantly with age in male WT mice (86), consistent with the reported elevations in tissue TSP1 and CD47 levels with aging (19,105,207,213). Thus, TSP1 physiologically opposes the activity of NO to regulate vascular tone, but this balance becomes perturbed with increasing age.…”
Section: +supporting
confidence: 73%
See 2 more Smart Citations
“…Mechanistic studies demonstrated that TSP1 blocked the dephosphorylation of myosin light chain-2 induced by treating these cells with NO and thereby promoted F-actin assembly and contraction of the smooth muscle cells. Notably, the elevated tissue cGMP levels found in young male Thbs1 -/-mice persisted as those mice were aged to 12-16 months, but cGMP levels fell significantly with age in male WT mice (86), consistent with the reported elevations in tissue TSP1 and CD47 levels with aging (19,105,207,213). Thus, TSP1 physiologically opposes the activity of NO to regulate vascular tone, but this balance becomes perturbed with increasing age.…”
Section: +supporting
confidence: 73%
“…The ability of a CD47 antibody and antisense morpholino suppression of CD47 to restore normal ischemic injury responses to aged WT mice is proof of principle that therapeutics targeting this pathway could have broad clinical applications (86,213).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate our model of renal IRI, we exposed wild-type (WT) mice to titrated degrees of bilateral renal ischemia (10,15, and 20 minutes), as we have reported, 18,26 and assessed renal injury at 1, 3, or 7 days after reperfusion. Ten minutes of warm ischemia had minimal effect on renal function, whereas serum creatinine was moderately increased after 15 minutes of ischemia at 24-hour reperfusion but returned toward baseline by 7 days (Figure 1a).…”
Section: Cd47 Limits Acute and Subacute Renal Recovery In Irimentioning
confidence: 98%
“…Levels of TSPs increase in multiple tissues with age (21, 116, 179-182). The significance of this increase in TSPs production is still unclear, although in some tissues it appears to be beneficial (21, 26, 179, 180).…”
Section: Introductionmentioning
confidence: 99%